Contagion and contact: social distancing, isolation, and crime in Ticino at Covid-19 times (Altre Modernità, 2023)
This paper aims to discuss, mainly in a descriptive way, the topic of contagion and contact from the perspectives of criminal law and criminology.First, the research offers an overview of the use of contagion and contact in the two disciplines. Whereas criminal law uses and interprets the term contagion primarily in relation to the infiltration of organized crime into economic and state apparatuses, criminology studies the effects of contact between victims and perpetrators on the likelihood of a crime occurring, and of behavioural contagion on the propensity to commit crime.Secondly, the article focuses on how lack of contagion and contact, which occurred because of restrictions to contain the Covid-19 pandemic, affected crime. The analysis of the international literature identifies the main interpretative hypotheses, which are then tested by analyzing crime data in Canton Ticino.In general, the international dynamics are confirmed in the Swiss Canton: between March and June 2020 crime decreased by 43.1 percent compared to the 2018-2019 average. This is mainly explained by the lack of contact between victims and offenders leading to fewer criminal opportunities. Also emerging is the importance of "time-shift" – the need to distinguish between short- and long-term effects on crime – and of "crime specificity" – the importance of delving into specifics related to crime types.
Keywords: contagion; contact; crime; Covid-19; criminal law; criminology